2020
DOI: 10.20527/flux.v1i1.7689
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Perbandingan Kandungan Fe dan Karakteristik Sifat Listrik Pasir Besi Sungai dan Pantai

Abstract: Penelitian ini bertujuan untuk mengetahui perbandingan kandungan Fe dan karakteristik sifat listrik pasir besi sungai dan laut yang disintesis di Kecamatan Pringgabaya. Sampel pasir besi sungai dan laut kemudian dipisahkan menggunakan magnet permanen, setelah itu dicuci menggunakan aquades dan di keringkan selama 2 jam pada temperatur 2000C. karakterisasi material pasir besi sungai dan laut kemudian di lakukan menggunakan AAS (Atomic Absorption Spektrometri), 2 titik probe, dan LCR meter untuk mengukur konstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Research location map is shown by Figure 1. Magnetic mineral samples were taken at 10 meters from the shoreline (for coastal sand) and from the riverbank (for river sand [2,7]. Magnetic mineral samples based on coastal sand and river sand then were analyzed at the Physics Laboratory of UIN Mataram for analysis using SEM-EDX, and BPTP NTB for analysis using AAS.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research location map is shown by Figure 1. Magnetic mineral samples were taken at 10 meters from the shoreline (for coastal sand) and from the riverbank (for river sand [2,7]. Magnetic mineral samples based on coastal sand and river sand then were analyzed at the Physics Laboratory of UIN Mataram for analysis using SEM-EDX, and BPTP NTB for analysis using AAS.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Indonesia also has many rivers. Coastal and rivers have very high iron sand potential [2]. In addition, Indonesia consists of several islands, one of which is Lombok Island in West Nusa Tenggara (NTB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can occur due to the process of transportation by water until it arrives at the river can break the grain. The color of iron sand in rivers can vary, but usually has a brighter color than the color of iron sand in coastal areas (Didik et al, 2020;Nugroho & Basit, 2014).…”
Section: Rivermentioning
confidence: 99%
“…Many studies on iron sand carried out on river iron sand, such as iron sand in the Brantas river and iron sand in the Boli Kiba river in West Kalimantan, as well as beach sand and river sand in the Ketapang and Sungai beaches in the Pringgabaya area [16]. This research was conducted to identify the content of iron sand and to determine the mineral content in river iron sand to reduce the levels of phosphate ions in the water and to analyze the ratio of iron content in beach and river sand [4].…”
Section: Introductionmentioning
confidence: 99%